P-149 Talking about sex and relationships: young people with life-limiting and life-threatening conditions speak out. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Blackburn, Maddie; Earle, Sarah; Watts, Lucy; Cooke, Alison; Than, Claire De
Abstract : Background: Due to advances in medical treatment and care, increasing numbers of young people with life-limiting or life-threatening conditions (LLTCs) are surviving into adulthood (Beresford & Stuttard, 2014). Growing evidence suggests that they are not always equipped to do so. There is an absence of tailored support in the important area of sex, intimacy and relationships (Blackburn, 2018) To address this gap, our research has informed the publications of guidance and standards and the development of on-line education resources (OERs) about relationships, intimacy and sex, via The Open University's Open Learn Portal. Sex, intimacy and relationships are central to all four phases of the transition journey. Many family members, carers and professional staff often feel unequipped to develop services that meet these needs (Blackburn, Chambers, Earle, De Than et al, 2016). Aims: The project aims to support young people within this often neglected and important area of transition into adult life. The development of OERs will help to overcome an absence of services and support in this field. Our research shows that people want to talk about sex, with family, carers or professional support staff. Methods: Adopting an inclusive approach and working in partnership with individuals with LLTCs, service providers and other organisations, the development of the OERS about sex are being co-designed and presented by disabled people, particularly those, with LLTCs. Results: The (OERs) are nearing completion and will be available for presentation at the forthcoming conference. The OERs include discussions by people with LLTCs who are either in relationships or would like to be intimate or to have sex. Topics include access to information about sex throughout life, taboos about sex, practicalities of intimacy for disabled people, sex aids and aspects of the law and governance. Conclusion: The OERs will help young people and their supporters address this invisible topic through knowledge, resources and lead to a better understanding of their views and experiences.